Utilization of Kluwih Seed Starch (Artocarpus camansi) as an Alternative Growth Medium for Aspergillus niger Fungus - saadah siregar; HAFIKA DALIMUNTHE; VINCENTIA ADE RIZKY (Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Carbohydrates in kluwih seeds have sufficient nutrients, such as potatoes and tubers, making it possible to be used as a medium for mushroom growth. The nutritional composition of breadfruit contains 25% carbohydrates, 1.5% protein, and 0.3% fat. Aspergillus niger fungi require nutrients such as carbohydrates and protein to grow. This study aims to determine whether kluwih seed starch can be used as an alternative medium for the growth of Aspergillus niger fungi. Method: This study used a pre-experimental design with laboratory observation. The study was conducted by utilizing kluwih seed starch as a medium, compared to Potato Dextrose Agar (PDA) and Sabouraud Dextrose Agar (SDA). Results: The results showed that kluwih seed starch can be used as an alternative medium for the growth of Aspergillus niger, with fungal colonies that grow macroscopically and microscopically almost the same as PDA and SDA media. Conclusion: Kluwih seed starch can be an alternative substitute for PDA media for the growth of Aspergillus niger.